FORECAST OF FLIGHT SEVERITY SITUATION WITH AN ENGINE FAILURE ON THE ASCENDING MANEUVERS BASED ON COMPUTATIONAL-EXPERIMENTAL DATA AND EXPERT JUDGMENT - D. V. Tikhonov; V. N. Tikhonov (Научный вестник МГТУ ГА, 2016)
The article is devoted to an assessment of danger degree of a flight situation with the engine failure on the ascending maneuvers using natural- model approach and expert evaluation in the absence of the possibility of using a pilotage stand.